Measuring community empowerment in the development of tourism village: Evidence from Batu City, Indonesia - Rahman, A. Faidlal; Wardana, Azna Abrory; Mufarrohah (Bahasa Indonesia, 2025)
Transforming villages into tourism villages is essential for community empowerment, enabling them to grow and manage local potential, although its implementation is not yet systematic. This research aims to measure the community empowerment in the development of tourism villages in Batu City, focusing on four villages: Sidomulyo, Bumiaji, Punten, and Tulungrejo. The measurement is carried out using the concept of Resident Empowerment through Tourism Scale (RETS) with modifications by adding an economic dimension. The research uses a quantitative descriptive approach, utilizing a purposive sampling technique to gather data from 100 respondents involved in tourism-related activities. The results indicate that psychological empowerment recorded the highest score 4.47, indicating strong community awareness, pride, and concern for tourism village potential. The social empowerment followed with a score of 4.37, reflecting active participation, collaboration, and community cohesion in tourism activities. The economic empowerment scored 3.95, demonstrating the community’s ability to leverage tourism for income generation and economic growth. Meanwhile, the political empowerment received a score of 4.05, showing community involvement in policy-making and decision-making related to tourism village management. This research can be used by the Batu City Government as a basis for developing more systematic tourism village management policies and improving training for tourism village communities, while also helping tourism village managers strengthen their management strategies.